2015
DOI: 10.4236/ojog.2015.58065
|View full text |Cite
|
Sign up to set email alerts
|

Re-Laparotomy after Caesarean Section at Omdurman Maternity Hospital-Khartoum, Sudan

Abstract: Introduction: Caesarean section has avoidable morbidity which may lead to mortality especially in developing world. Caesarean section is a major operation which should be performed with maximum care and safety. Objectives: This study aimed to find incidence, indications, procedures and maternal outcome of re-laparotomy after caesarean delivery. Methods: This was a descriptive cross sectional prospective total coverage hospital based study conducted at Omdurman Maternity Hospital from June 2014 to January 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
(13 reference statements)
3
9
1
Order By: Relevance
“…The main surgical procedure performed during re-laparotomy in the current study was hysterectomy (15 cases) either alone (8 cases) or combined with ligation of the anterior division of IIA (7 cases).These results are similar to those quoted from other studies [8,17]. The time interval between CS and re-laparotomy was variable according to the indication of re-laparotomy.…”
Section: Limitation Of the Studysupporting
confidence: 80%
See 3 more Smart Citations
“…The main surgical procedure performed during re-laparotomy in the current study was hysterectomy (15 cases) either alone (8 cases) or combined with ligation of the anterior division of IIA (7 cases).These results are similar to those quoted from other studies [8,17]. The time interval between CS and re-laparotomy was variable according to the indication of re-laparotomy.…”
Section: Limitation Of the Studysupporting
confidence: 80%
“…The mean age of patients in the current study was 30.1 ± 9.3 years which is similar to patients' age in the study done by Fazari et al [8]. In the study done by Biswas et al, the mean age of patients was 25 years [14].…”
Section: Limitation Of the Studysupporting
confidence: 74%
See 2 more Smart Citations
“…10 It has been observed that though infections after the primary surgery are localized to abscesses and perforation of the colon, systemic diseases such as pneumonia should not be ignored and treated effectively, so as to avoid systemic sepsis, and inflammatory responses and multiple organ failures. 10 Burst abdomen was seen only in 2 cases in our study accounting for 5.6%, while in a study by Fazari et al it was 8.8% 14 and another study in Ghana reported 4.17%. 16 Majority of the repair carried out in the surgeries was drainage and suturing of the hemorrhages including intestinal, postpartum and rectus sheath hematoma (66.7%) and 5 women underwent total hysterectomy (13.9%).…”
Section: Discussioncontrasting
confidence: 46%